Earnings management to avoid earnings decreases and losses : an exploration across the world - Santana, Verônica de Fátima; Sarquis, Raquel Wille (Revista Catarinense da Ciência Contábil, 2021)
This study evaluates the prevalence of earnings management to avoid losses and earnings decreases across the World. This practice was first documented by Burgstahler and Dichev (1997) for United States firms from 1976 to 1987. We replicate their study for a more recent and global sample. Firms that do not seem to manage earnings do avoid reporting earnings decreases, but we found persistent evidence of earnings management to avoid reporting losses. The results are consistent across different geographical regions, countries, and before and after International Financial Reporting Standards (IFRS) adoption. Unlike Burgstahler and Dichev (1997), however, we were not able to find evidence on which components of earnings (cash flow from operations, changes in working capital, or other accruals) firms mainly manage to increase earnings, concluding they likely use a bundle of all these components. Our results are important mainly to financial analysts and general investors, who should be careful in giving good prospects to firms who presented small profits since they are likely small losses artificially managed to look better, a practice widely spread across time and geographical regions among IFRS adopters and non-adopters.